Isocyanate–free tannin–based polyurethane resins for enhancing thermo-mechanical properties of ramie (Boehmeria nivea L.) fibers - Lubis, Muhammad Adly Rahandi; Aristri, Manggar Arum; Sari, Rita Kartika; Iswanto, Apri Heri; Al-Edrus, Syeed Saifulazry Osman; Sutiawan, Jajang; Lee, Seng Hua; Antov, Petar; Kristak, Lubos (Elsevier B.V., 2024)
The objective of this research was to investigate and evaluate the possibility of increasing the thermo-mechanical properties of ramie (Boehmeria nivea L.) fibers by impregnating them with a tannin-based non-isocyanate polyurethane (Bio-NIPU) resin. The resin was created by reacting tannin of Acacia mangium with dimethyl carbonate (DMC) and hexamethylenediamine (HMDA). The optimal time of impregnation was discovered to be 90 min, as demonstrated by its thermal stability, with a residual of 25 remaining after being treated to a temperature of 750 °C. When ramie fibers were impregnated with the newly developed tannin-based Bio-NIPU resin, their thermal and mechanical qualities significantly enhanced. In terms of mechanical properties, the impregnated ramie fibers had a tensile strength of 325 MPa and an elasticity modulus of 10.82 GPa. Py-GCMS was used to confirm the production of urethane groups as a result of the reaction between the tannin-based Bio-NIPU resin and ramie fibers. The use of FE-SEM in conjunction with EDS allowed the detection of nitrogen from urethane groups in Bio-NIPU. The characterization analysis also demonstrated that incorporating tannin-based Bio-NIPU resin into ramie fibers had a substantial impact on their thermal and mechanical properties, increasing their potential for wider use across varied industrial sectors.